PENGARUH KELAS AYAH TERHADAP PENGETAHUAN TUMBUH KEMBANG ANAK DI RS HERMINA YOGYA - Syarif Hidayatullah Al Bahri; Nurina Mutia Farah; Indri Kurniawati; Iklima Anggarani Purbaningrum; Hilda Amalia; Moh Heri Kurniawan (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2025)
The role of fathers in early child development is crucial but still not fully understood or implemented in Indonesia. The focus has traditionally been on mothers, often neglecting the father’s role. The Father’s Class is an intervention that provides education to fathers of newborns at Hermina Hospital Yogyakarta, using leaflets and explanations from doctors or midwives about infant growth and development during the first month. The aim of this study is to assess the knowledge level and the impact of the Father’s Class intervention on child development at Hermina Hospital Yogyakarta. This is an observational analytical study with a case-control design, conducted at Hermina Hospital Yogyakarta. The sample was taken through consecutive sampling. A total of 30 samples were needed, divided into two groups: 15 in the case group and 15 in the control group. The case group will receive the Father’s Class intervention, which lasts about 30 minutes and is conducted once when the mother and baby are in the joint care room. The Father’s Class intervention was more effective in increasing the respondents' knowledge about child development. Most respondents in the case group showed improved knowledge after receiving the intervention.